Protocol of the CONSORT and SPIRIT Extension for multicenter clinical trials - Zhang, Xuan; Dong, Chongya; Wang, Nana; Chan, Chunpong; Lau, Chung Tai; Wang, Juan; Miao, Jiangxia; Yao, Chen; Li, Youping; Lyu, Aiping; Moher, David; Bian, Zhaoxiang (Frontiers in Public Health, 2023)
Background: Multicenter clinical trials play an indispensable role for assessing the efficacy of a new intervention or treatment, particularly in Phase II or III studies. Previous studies have shown that these studies often suffer from inadequate reporting of key details related to their design, implementation, and analysis, both in the protocol and final reports. This limitation reduces the practical and scientific value of the findings. Furthermore, the lack of guidance on how to report multicenter features can contribute to poor reporting. Therefore, this study aims to develop guidelines to improve the reporting 2 2 of multicenter trials, including two Extensions of the CONSORT 2010 and the SPIRIT 2013. Methods/design: The standard methodology for developing health research reporting guidelines involves the following steps: i) Identifying the need for development and launching the research project; ii) Preparing the registration and reviewing the literatures; iii) Proposing the initial Checklists and conducting the Delphi exercise; iv) Arranging the consensus meeting and formulating the Checklists; v) Conducting the pilot test and drafting explanatory documents (E&E); vi) Seeking comments from advisory group and finalizing the guidelines; and vii) Developing the publication and dissemination strategies. Conclusion: By using the CONSORT and SPIRIT checklists as starting points, the development of extensions specific to multicenter trials can help researchers design and report high-quality clinical research. This, in turn, can facilitate the application of study findings in the current evidence-based healthcare system.